Perspectives on mitochondrial relevance in cardiac ischemia/reperfusion injury - Pedriali, Gaia; Ramaccini, Daniela; Bouhamida, Esmaa; Wieckowski, Mariusz R.; Giorgi, Carlotta; Tremoli, Elena; Pinton, Paolo (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular disease is the most common cause of death worldwide and in particular, ischemic heart disease holds the most considerable position. Even if it has been deeply studied, myocardial ischemia-reperfusion injury (IRI) is still a side-effect of the clinical treatment for several heart diseases: ischemia process itself leads to temporary damage to heart tissue and obviously the recovery of blood flow is promptly required even if it worsens the ischemic injury. There is no doubt that mitochondria play a key role in pathogenesis of IRI: dysfunctions of these important organelles alter cell homeostasis and survival. It has been demonstrated that during IRI the system of mitochondrial quality control undergoes alterations with the disruption of the complex balance between the processes of mitochondrial fusion, fission, biogenesis and mitophagy. The fundamental role of mitochondria is carried out thanks to the finely regulated connection to other organelles such as plasma membrane, endoplasmic reticulum and nucleus, therefore impairments of these inter-organelle communications exacerbate IRI. This review pointed to enhance the importance of the mitochondrial network in the pathogenesis of IRI with the aim to focus on potential mitochondria-targeting therapies as new approach to control heart tissue damage after ischemia and reperfusion process.